STRATEGIES TO IMPROVE SPEAKING SKILL FOR TOURISM STUDENTS - Dhea Saragih; Olina Putri Batubara; Vanessa Pritin Angel Halawa; Sabarni Rodearni Sipayung; Selviana Napitupulu (GoAcademica Research dan Publishing, 2022)
This research was conducted with the aim of channeling information about learning strategies that educators can use to provide speaking teaching to students majoring in tourism. The instrument to collected the data in this research is by doing a library research. Through library research, researchers carry out activities by finding materials related to this research. The data collection technique used in this research is library research. This is an activity to collect materials related to research originating from books, scientific journals, literatures and other publications, which are worthy as the sources for research that the researchers examined, by describing the data through some opinions of experts. Using qualitative approach in this research is expected to provide a comprehensive facts about strategies to improve English speaking skill for tourism students. The benefit of this research is to add insight to readers, especially for the educator, regarding the role of learning strategies to increase speaking skills in the tourism sector.